Navigating collaborative open innovation projects: Staging negotiations of actors' concerns. (6th April 2022) - Pedersen, Signe; Bogers, Marcel L. A. M.; Clausen, Christian
Abstract : Open innovation has attracted significant attention as companies respond to increasing innovative complexities by opening their organizational boundaries to interact with stakeholders along the innovation funnel. However, knowledge from customers and users is not always easily translated into solutions that can be commercialized. Micro‐level challenges of open innovation projects that might be impeding commercialization remain under‐explored in the literature. To address this research gap, we use a collaborative staging approach inspired by actor‐network theory to focus on micro‐level negotiations of actors' concerns at the project level. Analysing data collected via ethnographic research and participant observation in a longitudinal qualitative case study, we investigate how managers and designers navigated value creation and capture when conceptualizing an app for hospitalized stroke patients. Our findings reveal an action‐oriented staging approach to collaborative open innovation efforts and selective enactment of business models depending on whether the focus is value capture or value creation. Furthermore, we point to a repertoire of staging moves that managers and designers can use to facilitate productive negotiations and network alignment as value creation opportunities co‐evolve and to conceptualize value offers in collaborative open innovation processes.